An Unspecific Dog: Artifacts of This Late Stage in History - Rothes, Joshua (punctum books, 2017)
A nationwide survey conducted by an institute for philosophical research has determined that nihilists, on the whole, have good intentions. In An Unspecific Dog, Joshua Rothes collects 150 short texts as fables for our time, a veritable catalog of agnotology, a series of situations and propositions that revel in the dark irony at the root of our early-twenty-first-century existence. A man reads the terms and conditions and finds that he has no secrets, while scientists promise that, "with improvements to fMRI technology, what matters to us will become more clear." The subjects of these texts are caught between vocabularies, between contingency and certainty, the interim in which certain kind of ironic vitality exists, where tragedy and humor are equally likely and often deeply entangled. Rothes reminds us that language acts as a mirror for human experience, in that through it we can never really see the backs of our own heads.